THE REASONS OF MALE AND FEMALE’S WAY IN COMMUNICATION USED BY INDONESIAN FOOD VLOGGER - Dina . Hanifa; Anni Holila Pulungan; Rahmad . Husein (LINGUISTIK TERAPAN, 2023)
This article was discussed about the reasons of male and female’s way in communication by Indonesian food vlogger “Ken and Grat” based on Basow and Rubenfield theory. They were assertive, power-hungry, expressive, tentative, and polite. This article was aimed to found the reasons why the food vlogger “Ken and Grat” used the ways in the way they are in communication. This article used Lakoff theory to found that reasons. This   article applied descriptive qualitative method. The data of this research were taken from the vlog videos on youtube and the video transcript. The results have revealed that there are four reasons why the food vlogger “Ken and Grat” used the ways in the way they are in communication are namely culture, stereotype, confidence, and society. And from all of the reasons, the most dominant reason was society both by male and female.